Budaya Kerja dan Implikasinya terhadap Pola Interaksi Serta Etos Kerja Pegawai - Ismail Aziz, Widodo Dwi; Seto Prawira, Ario (UIN Sunan Gunung Djati Bandung, 2026)
This research aims to examine how work culture influences employe interaction patterns and work ethic in creating a productive and sustainable work environment. The research uses a descriptive qualitative approach thru literature review from journals, books, and academic publications related to work culture, work ethic, and work life balance. Analysis was conducted thru data reduction, presentation, and qualitative conclusion drawing. The results show that a positive work culture characterized by openness, cooperation, and mutual respect encourages harmonious interactions and enhances work ethic. Work life balance also plays a role in maintaining performance consistency and employe well being. Additionally, management support thru policies and supportive leadership becomes a key factor in building a healthy and sustainable work culture.